Zirconium in the Nuclear Industry: 18th International Symposium 2018
DOI: 10.1520/stp159720160068
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iron on Dislocation Evolution in Model and Commercial Zirconium Alloys

Abstract: While the evolution of irradiation-induced dislocation loops is well correlated with irradiation-induced growth phenomena, the effect of alloying elements on this evolution remains elusive, especially at low fluences. To develop a more mechanistic understanding of the role of Fe on loop formation, state-of-the-art techniques have been used to study a proton-irradiated Zr-0.1Fe alloy and proton-and neutronirradiated Zircaloy-2. The two alloys have been irradiated with 2 MeV protons up to 7 dpa at 350 °C and Zir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 67 publications
6
17
0
Order By: Relevance
“…The binary 1.5 dpa Zr-0.1Fe alloy used in this work has been investigated in detail as part of another study, looking into the effect of redistributed Fe from SPPs on dislocation densities [20]. It was found that this alloy contains ~1-2 μm coarse Zr 3 Fe secondary phase particles (SPPs) unevenly distributed throughout the sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The binary 1.5 dpa Zr-0.1Fe alloy used in this work has been investigated in detail as part of another study, looking into the effect of redistributed Fe from SPPs on dislocation densities [20]. It was found that this alloy contains ~1-2 μm coarse Zr 3 Fe secondary phase particles (SPPs) unevenly distributed throughout the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Close to these SPPs, which have undergone some irradiation-induced dissolution, Fe has been observed to segregate to pyramidal loops with a likely Burgers vector of ! " 1123 [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe segregation can stabilize a-type loops as evidenced by the results above, which may impede the transition from the aligned a-type loops to a coarse c-component loop. This may explain why c-component loop nucleation is delayed in Zr-Fe alloys, in comparison to pure Zr, as reported by Topping et al[83]. In addition, the enhanced stabilization of atype loops by the presence of Fe could prevent the absorption of a-type loops by the GBs.…”
mentioning
confidence: 53%
“…The collision cascade induced a rotation and gradual glide towards the GB, which led to eventual absorption by the GB as illustrated in Figure 8 (e). The importance of Fe alloying on the formation of -component loops was discussed by Carlan et al [82], and a recent study by Topping et al [83] suggested that an increase in Fe content in a Zr alloy delays -loop nucleation. Here, the effect of Fe on the loop stability is explored.…”
Section: The Stability Of An -Type Vacancy Loop Near the Tilt Gb Durimentioning
confidence: 99%